Comparison of oocyte mRNA localization patterns in sterlet Acipenser ruthenus and African clawed frog Xenopus laevis - Pocherniaieva, Kseniia; Sidova, Monika; Havelka, Milos; Saito, Taiju; Psenicka, Martin; Sindelka, Radek; Kaspar, Vojtech (Journal of experimental zoology. Part B, Molecular and developmental evolution, 2018)
In oocytes, RNA localization has critical implications, as assembly of proteins in particular subcellular domains is crucial to embryo development. The distribution of mRNA molecules can identify and characterize localized transcripts. The goal of this study was to clarify the origin of primordial germ cells in the oocyte body plan and to reveal the generation of cell lineages by localized RNAs. The distribution of 12 selected mRNAs in sterlet Acipenser ruthenus oocytes was investigated by qPCR tomography and compared with known patterns of mRNA localization in Xenopus laevis. We investigated the distribution of two gene clusters in the ooplasm along the animal-vegetal axis of the sturgeon oocyte, both of which showed clearly defined intracellular gradient pattern remarkably similar to their distribution in the frog oocyte. We elucidated the localization of sturgeon egg germplasm markers belonging to the vegetal group of mRNAs. The mRNAs coding otx1, wnt11, and veg1 found to be localized in the sturgeon animal hemisphere are, in contrast, distributed in the vegetal hemisphere in amphibian. Actinopterygii and Sarcopterygii, two major lineages of osteichthyan vertebrates, split about 476 Ma (Blair & Hedges, ), albeit basal lineages share conserved biological features. Acipenseriformes is one the most basal living lineages of Actinopterygii, having evolved about 200 Ma (Bemis, Birstein, & Waldman, ), contemporaneous with modern amphibians (Roelants et al., ).
Keywords: Animals; biologická evoluce; primordial Germ Cells; sturgeon; druhová specificita; Oocytes; Xenopus; Protein Transport; acipenser ruthenus; qPCR; Fishes; Species Specificity; oocyty; messenger RNA; ryby; RNA, Messenger; transport proteinů; xenopus laevis; RNA localization; zvířata; oocyte; Biological Evolution